HOMO SCRIBENS IN THE MIRROR OF ORRESPONDENCE OF VASYL STEFANYK - Кочерга, С. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
Derrida's and M. Epsteir’s theory of writing as a mode of being became the basis of this article. It analyzes the correspondence of Vasyl Stefanyk, in particular the transsubjective hypostasis of scriptorium in the way the Ukrainian writer understood it. The main task of the article is to comprehend the anthropological aspects of the act of writing in the light of epistolary of Stefanyk. Attention is paid to the reflexivity in the private letters of the writer, as well as confessional tone, exceptional openness self-characteristic. The research contains the hermeneutic analysis of metaphors that attribute the transcendence of the birth of artistic images and frustration because of discord between the conceived and the written. It marks the Stefanyk's principle of separating of "literature" with dominate marketing component. Stefanyk's letters convincingly illustrate the thesis of the importance of the exemplary reader for incessant creative intentions. His friend V. Moraczewski became such a perfect recipient that the original writer's style formed through their dialogues. The article suggests that the author's self-image contains the Borges's type homo legens that chastises the writing of the God. However, Stefanyk focuses on the discovering of the universe construction through the comprehension of the marks of its small piece that is his homeland. Stefanyk's expressionist poetics keeps the tracks of high-energy commitment of the scriptor. The ecstatic state of the demiurge is the quintessence of realization of homo scribens.